2006
DOI: 10.1080/10485230609509711
|View full text |Cite
|
Sign up to set email alerts
|

Green Building Design for Schools—The Next Time Around

Abstract: Special care must be applied to the proper planning and design of public school facilities. Student populations for this age group are prone toward high levels of inner ear deficiencies, and they struggle in difficult acoustical environments. Additionally, students with asthma conditions must contend daily in building environments with marginal ventilation systems. What can be done? Schools must be free from unnecessary ambient noise and indoor air pollutants. The design professional must provide extraordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Unfortunately preliminary studies or the first value engineering session typically try to rule this option out due to higher construction costs. Hence, distributing from the ceiling and returning low is sometimes utilized as a compromise (Johnson et al, 2005)." The prototype construction was planned, developed and constructed in order to realize most of the above features.…”
Section: Green and Climate Responsive Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately preliminary studies or the first value engineering session typically try to rule this option out due to higher construction costs. Hence, distributing from the ceiling and returning low is sometimes utilized as a compromise (Johnson et al, 2005)." The prototype construction was planned, developed and constructed in order to realize most of the above features.…”
Section: Green and Climate Responsive Buildingsmentioning
confidence: 99%
“…It has to be noted that a comfortable indoor climate in school not only helps to retain students in the school but also contributes towards better performance of the students. Research has shown that the best temperature range and humidity for reading and learning is between 68 F and 74 F and 40-60%, respectively (Johnson et al, 2005). Issa et al (2011) conducted a study aimed to compare a number of quantitative and qualitative aspects of usage across a sample of 10 conventional, 20 energy-retrofitted and three green Toronto schools.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that teachers are happier when they have the ability to control their environment. Healthy and happy teachers save schools money and perform better in teaching [29]. In contrast, a school with inadequate lighting design might demote students' ability of learning.…”
Section: Natural Light and Students' Academic Performancementioning
confidence: 99%